PREPARING FINANCIAL STATEMENTS FOR MSEs: THE COACHING ASSISTANCE IN ULU SADDANG VILLAGE OF SOUTH SULAWESI - Frihatni, Andi Ayu; Faisal, Andi; Yassin, Muhammad; Amaliyah, Umi; Wulandari, Yusma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This community service helps and guides individuals or small entrepreneurs, especially micro and small enterprises (MSEs) Ulu Saddang Village, Lembang District, Pinrang Regency. This study aims to describe the community program. The method of this community uses Participatory Action Research. Some approaches are classical form with a discussion, question and answer, and simulation with the intention that the material which can be well received by society. It is hoped that after this service program, the participants will have knowledge and insight as small entrepreneurs who are skilled in managing finances and also find opportunities to increase family finances as a provision to improve their standard of living to be better.